Clinical Features and Long-Term Outcomes of Living Donors of Liver Transplantation Who Developed Psychiatric Disorders - Shizuku, Masato (Ann Transplant, 2020)
BACKGROUND: In the field of living donor liver transplantation (LDLT), it is important to ensure donor’s psychological well-being. We report on clinical features and long-term outcomes of LDLT donors who developed psychiatric disorders after their donor operations. Additionally, we compare patient backgrounds, as well as surgical and perioperative aspects between LDLT donors with and without postoperative psychiatric complications. MATERIAL/METHODS: Between November 1998 and March 2018, we identified 254 LDLT donors at our hospital. Among these, we investigated those who had newly developed psychiatric complications and required psychiatric treatment after donor operation. RESULTS: The median duration of follow-up was 4 years. Sixty-five donors were lost to follow-up. Eight donors (3.1%) developed postoperative psychiatric complications, including major depressive disorder in 4, panic disorder in 2, conversion disorder and panic disorder in 1, and adjustment disorder in 1. The median duration from donor surgery to psychiatric diagnosis was 104.5 days (range, 12 to 657 days) and the median treatment duration was 18 months (range, 3 to 168 months). Of those, 3 donors required psychiatric treatment over 10 years, and 4 donors remained under treatment. The duration of hospital stay after donor operation was significantly longer and perioperative complications with Clavien classification greater than grade IIIa were more frequent in donors with psychiatric complications than in those without psychiatric complications (P=0.02 and P=0.006, respectively). CONCLUSIONS: Accurate diagnosis and appropriate treatment for psychiatric disorders by psychiatrists and psychologists are important during LDLT donor follow-up. Minimization of physiological complications might be important to prevent postoperative psychiatric complications in LDLT donors.